2011
DOI: 10.1007/s11664-011-1727-5
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Reactions in Sn/Fe-xNi Couples

Abstract: The interfacial reactions between Sn and several Fe-xNi alloys were investigated in this study. Two different FeSn 2 phase types formed at the Sn/Fe-40.8 at.%Ni (Sn/alloy 42) interface. When the Ni content of the Fe-Ni alloy was less than 80 at.%, only the FeSn 2 phase with layer structure could be formed at the interface. When the Ni content was increased to 80 at.% to 90 at.%, both FeSn 2 and Ni 3 Sn 4 phases formed in the Sn/Fe-xNi couples. When the Ni content was larger than 95 at.%, only the Ni 3 Sn 4 pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Although FeSn is also shown as a stable IMC in the Fe-Sn binary phase diagram, FeSn IMC was not identified [12]. This result is consistent with the observations in other Sn-containing solder/ferrous metal reaction systems [13][14][15].…”
Section: Microstructural Evolution Of the Intermetallic Compound Layersupporting
confidence: 81%
“…Although FeSn is also shown as a stable IMC in the Fe-Sn binary phase diagram, FeSn IMC was not identified [12]. This result is consistent with the observations in other Sn-containing solder/ferrous metal reaction systems [13][14][15].…”
Section: Microstructural Evolution Of the Intermetallic Compound Layersupporting
confidence: 81%
“…Figure 2A is an example of non-equilibrium NiSn4 formed at the interface during solid Figure 2B). In contrast, when soldered to Alloy42, the FeSn2 interfacial intermetallic layer serves as an efficient diffusion barrier limiting the amount of Ni that dissolves into the liquid solder during reflow [28,29].As result, this type of solder joints has less NiSn4 in the bulk solder than on Ni or ENIG substrates( Figure 2D). We have also found that trace Fe additions promote metastable NiSn4 formation due to epitaxial nucleation of NiSn4 on FeSn2 particles [30].…”
mentioning
confidence: 99%
“…FeNi alloys [15], and could transformed from (Ni,Fe)3Sn4 into FeSn2 phase when the Fe content in the Fe-Ni layer was between 10% to 12.5% [16]. The Sn-Bi and Sn-Cu eutectic solders reacted with the Fe-Ni substrate.…”
Section: Interfacial Microstructure After Reflowmentioning
confidence: 99%
“…Early studies on the Fe-Ni alloy are mainly about the brazing or solid bonding processes. Recently, a few publications have reported on the interfacial reactions between Sn based solders and Fe-Ni alloys, discussing its potential application as UBM layer for Sn-based solders [7][8][9][10][11][12][13][14][15][16]. It is reported that the FeNi layer has an acceptable wettability for SnAgCu (SAC) solder with or without an adequate pre-treatment in soldering [7], exhibiting a slower interfacial reaction rate compared to the traditional UBMs [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation